2004
DOI: 10.1021/jp040047x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Vibrations at Surfaces with Back-Bonds Nearly Parallel to the Surface

Abstract: It has been discovered that several very different surfaces exhibit a common property:unusually large vibration amplitudes of the outermost atoms, well beyond the enhancement normally expected at typical clean surfaces. These special surfaces are: ice (010) and Si(111)-(2x1). The root-mean-square vibration amplitudes in these surfaces are at least double the bulk values. The common cause that may explain these vibration amplitudes is that the surface atoms (or molecules in the case of ice) only have back-bonds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…3). These results can possibly be rationalized in light of the previous observations and calculations showing that enhanced vibrations for specific surface geometries [26], as well as a poorer surface packing and first-neighbor bonding and coordination [1,5], favor surface melting. In our case, the backbonds nearly parallel to the surface Si(111) are able to induce surface premelting through large anisotropic vibrations, as also observed for other surfaces including ice (see Ref.…”
supporting
confidence: 56%
“…3). These results can possibly be rationalized in light of the previous observations and calculations showing that enhanced vibrations for specific surface geometries [26], as well as a poorer surface packing and first-neighbor bonding and coordination [1,5], favor surface melting. In our case, the backbonds nearly parallel to the surface Si(111) are able to induce surface premelting through large anisotropic vibrations, as also observed for other surfaces including ice (see Ref.…”
supporting
confidence: 56%
“…This illustrates that, after the incorporation of zinc, low symmetry monoclinic acanthite Ag 2 S undergoes rearrangement to higher symmetry orthorhombic and cubic AIS. The transformation of the crystals structure have been observed in many cases, which may be the comprehensive result of free energy, diffusion rate and cationic radius. , Structural relationship among monoclinic Ag 2 S, orthorhombic AIS, and cubic AIS is demonstrated in Figure S4.…”
Section: Resultsmentioning
confidence: 99%
“…The transformation of the crystals structure have been observed in many cases, which may be the comprehensive result of free energy, diffusion rate and cationic radius. 48,49 Structural relationship among monoclinic Ag 2 S, orthorhombic AIS, and cubic AIS is demonstrated in Figure S4.…”
Section: ■ Materialsmentioning
confidence: 99%
“…7 It has been observed that, at the nanoscale, there are changes in the reaction free energy and the height of the reaction barrier, relative to the bulk. 27,28 For instance, by analogy to quantum dots, in the thin precursor protonic titanate nanotubes, the width of the reaction zone can become comparable in dimension to the whole width of the nanotube, due to the relatively small number of atomic layers present within a few nanometers of the structure. Hence, the slow propagation of the reaction front, driven by the gradient of the local chemical potential at or near the reaction zone, may no longer be the rate-limiting step of the reaction.…”
Section: Resultsmentioning
confidence: 99%